2021
DOI: 10.3390/ani11092627
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Potential of Stone Moroko (Pseudorasbora parva, Temminck et Schlegel, 1846) (Teleostei: Cypriniformes: Gobionidae) Inhabiting Central Europe

Abstract: Similar to other invasive species, stone moroko is extending its global distribution. The present study aimed to assess the reproductive potential of stone moroko fish in a new habitat in Poland based on analysing the sexual cycle and fecundity. Fish morphometric data, age, and gonadal structures were analysed. Fish age ranged from 0+ to 5+ years. Most females and males (93% and 60%, respectively) had reached sexual maturity in the first year of their life, with the smallest length of 25 mm and 28 mm, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…From there, the species was able to spread westward throughout the Danube Basin (Gozlan et al, 2010). P. parva exhibit highly plastic life‐history traits, including early maturity, short life span, sexual dimorphism in body size, batch spawning and male nest guarding behaviour (Gozlan et al, 2010; Kirczuk et al, 2021). Adding its tolerance of a wide range of environmental conditions (Pinder et al, 2005), the species possesses many characteristics of a successful invader and it was experimentally shown that small numbers of founders might be sufficient to start a biological invasion (Britton et al, 2015) and have measurable impact on the ecosystem already at low densities (Jackson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From there, the species was able to spread westward throughout the Danube Basin (Gozlan et al, 2010). P. parva exhibit highly plastic life‐history traits, including early maturity, short life span, sexual dimorphism in body size, batch spawning and male nest guarding behaviour (Gozlan et al, 2010; Kirczuk et al, 2021). Adding its tolerance of a wide range of environmental conditions (Pinder et al, 2005), the species possesses many characteristics of a successful invader and it was experimentally shown that small numbers of founders might be sufficient to start a biological invasion (Britton et al, 2015) and have measurable impact on the ecosystem already at low densities (Jackson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%